ASSESSMENT OF PSYCHOEMOTIONAL STATE IN CHRONIC HEADACHES: INTERGROUP ANALYSIS USING THE HADS SCALE (Medical science of Uzbekistan, 2025)
Relevance. Headache is one of the most common medical conditions worldwide. Migraine, chronic tension-type headache, and medication-overuse headache significantly affect patients' quality of life. This study assessed the psychoemotional state of patients based on headache types.  To evaluate anxiety and depression levels using the Hospital Anxiety and Depression Scale (HADS) and analyze psychological changes associated with different types of headaches. Materials and Methods. The study involved 315 patients divided into four groups: migraine with aura, migraine without aura, chronic tension-type headache (CTTH), and medication-overuse headache. Anxiety and depression levels were assessed using the HADS scale, and intergroup differences were statistically analyzed. Results and Discussion. The study revealed higher levels of anxiety and depression in the migraine with aura and chronic tension-type headache groups. Subclinical depression was more frequently observed in the migraine without aura group compared to other groups. Clinical anxiety and depression levels were also significantly high in the medication-overuse headache group, indicating a strong impact of pain on emotional well-being. Conclusion. Assessing the psychological state of patients with headaches, providing psychological support, and implementing therapy aimed at reducing anxiety and depression is crucial. Integrating neurological and psychological approaches in migraine and headache treatment is essential for effective management.